IMPLEMENTASI KEGIATAN DIDIKAN SUBUH DALAM MENINGKATKAN KARAKTER RELIGIUS SISWA MI AL-HIKMAH PALEMBANG - Lathifa Amelia; Middya Boty; Ines Tasya Jadidah (STKIP Subang, 2026)
This research is motivated by the importance of building students' religious character through religious activities at school. One effort undertaken is through the dawn prayer activities at MI Al-Hikmah Palembang. This study aims to determine the implementation of dawn prayer activities, their role in improving students' religious character, as well as supporting and inhibiting factors in their implementation. This study uses a qualitative approach with a descriptive type. The research subjects consisted of supervising teachers, homeroom teachers, and students. Data collection techniques were carried out through observation, interviews, and documentation, while data analysis used the Miles and Huberman model which includes data reduction, data presentation, and drawing conclusions. The results show that dawn prayer activities are carried out routinely with a series of activities such as opening, reading the Qur'an, memorizing the pillars of faith and Islam, practicing the call to prayer and iqamah, reading prayer readings, collective dhikr, and delivering a sermon. This activity plays a role in improving students' religious character through habituating worship, instilling religious values, and training discipline, courage, and responsibility. Supporting factors include support from the school, teachers, and parents, while inhibiting factors include suboptimal student discipline and differences in student abilities. Thus, dawn prayer activities are effective in shaping the religious character of students in the madrasah environment.